Nephelium lappaceum Peel Extract Alleviates High Fat-High Fructose Diet-Induced Fatty Liver in Mice (Journal of Tropical Pharmacy and Chemistry, 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD) occurs due to excessive fat accumulation in the liver, triggered by high fat and sugar intake. This study aims to investigate the effect of Nephelium lappaceum peel extract (NLE) on hepatic profile in mice induced with a High Fat High Fructose Diet (HFHFD). The study involved 25 male mice divided into five groups: (1) normal group, (2) HFHFD group, (3) NLE 125 mg/kg bw, (4) NLE 250 mg/kg bw, and (5) NLE 500 mg/kg. HFHFD and NLE administration were carried out for 14 days. On the 15th day, mice were sacrificed and liver was harvested for further analysis. Descriptive analysis was performed for macroscopic and microscopic (histological) liver observations. ANOVA was used to analyze liver index. The results showed that NLE improve fatty liver both macroscopically and microscopically. The liver index also improved significantly in group treated by NLE 250 (p